lntegrating Message-Passing with Vector Architectures - Mendes, Celso L. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 1995)
Vector architecures proride excellent computational throughput, while successfully tolerating memory latency by pipelining memory accesses. In this paper, we propose a generalization of vector architectures to message-passing multicomputers, which combines the efficiency of vector computation with the scalablity of distributed-memory systems. In our proposed architecture, each node is a conventional vector processor (with chaining capability and pipelined functional units) augmented by native instructions to send and receive messages through vector registers. In this scheme, inter-node communication can be performed via vector-send/receive instructions, gaining the benefits of communication pipelining, reduced memory copies (memory-to-repter-to-register instead of memory-to-memory-to-cache), and lower communication latency (due to tight processor-communication coupling). We show that this strong integration between functional and communication units can lead to substantial performance improvement over conventional message-passing multicomputers. We model pipelined computation-communication systems both analytically and with a detailed construction-level simulation, and compare this simulation data with empirical results from an Intel Paragon. Preliminary data from a matrix multiplication example indicates our proposed vector-parallel architecture often significant scalability benefits over existing message-passing systems.